The cult of the quantifiable: the fetishism of numbers in higher education. (1st March 2021) - Wood, Felicity
Abstract : This paper examines the 'fetishism of numbers' (Gudeman, 1998, p.1) that has taken hold in restructured, market-oriented institutions of higher education. As all areas of academic life have been rendered down to the quantifiable, and university environments have become dominated by the rituals of counting, numbers have been imbued with a potency of almost preternatural proportions. The points of comparison between the power ascribed to the numerical in diverse mystical, magical practices and the overriding significance accorded to numbers in restructured universities are explored. When the near-obsessive focus on numbers is viewed as a form of fetishism, some of the reasons why numbers have been elevated to a position of excessive importance come to the fore, as does the illogical nature of such reasoning. Although numbers have been valorized on account of their ostensible accuracy, transparency, objectivity and impartiality, this study contends that the present-day fetishism of numbers in higher education is neither rational nor practical. Neither does it ensure fairness and accuracy. Instead, it stems from and fosters delusion, deception, inequity and irrationality, vanity and greed.